LNCaP prostate cancer cells are insensitive to zinc-induced senescence - Wong, P.F.; AbuBakar, Sazaly (2008)
Prostate cancer is an age-related disease that is linked to the inability of prostate cells to accumulate zinc following transformation. It is shown in the present study the the basal percentage of normal prostate cells expressing senescence-associated beta-galactosidase (SA-beta-gal) is higher than that of the cancer cells. In the presence of high zinc in the cell culture medium, the percentage of normal prostate cells expressing the SA-beta-gal increased but not that of the cancer cells. Increased intracellular zinc occurs in the prostate cancer cells treated with supraphysiologic concentration of zinc but it does not induce senescence or decrease the telomerase activities in these cells. Senescence, however, occurred when the prostate cancer cells DNA is damaged by irradiation. These findings suggest that prostate cancer cells are insensitive to the senescence-inducing effects of zinc but the cancer cells retain the capacity to undergo senescence through other pathways. (c) 2008 Elsevier GmbH. All rights reserved.